Model Integrasi Keilmuan Pesantren Pada Pendidikan Tinggi Keagamaan Islam Di Indonesia - Akhmad Shunhaji; Binti Khoiriyah (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2021)
This qualitative research on scientific integration in the Islamic Religious Higher Education in Indonesia (PTKI) departs from the main question, what is the model of integration with pesantren scientists at PTKI? The choice of PTKI to be the focus of this study was determined based on a purposive sampling technique that aimed at three state Islamic universities, namely UIN Jakarta, UIN Malang and IAIN Tulungagung. Because it was conducted during a pandemic, this research is not a pure field study. This study draws information from the available data supported by semistructural interviews and sporadic observations. The main conclusion in this study is the variety of pesantren models applied in PTKI as a non-formal education system. Each campus has the autonomy to apply the pesantrenan education model. The concept of implementing Madrasah Diniyah takmiliyah Al-Jami'ah at the Ministry of Religion has not or has not even become a reference for the three PTKINs studied. The three PTKIN that are the focus of this research have the same name for the implementation of pesantrenan education, namely